2014
DOI: 10.4161/rna.27990
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR adaptive immune systems of Archaea

Abstract: CRISPR adaptive immune systems were analyzed for all available completed genomes of archaea, which included representatives of each of the main archaeal phyla. Initially, all proteins encoded within, and proximal to, CRISPR-cas loci were clustered and analyzed using a profile–profile approach. Then cas genes were assigned to gene cassettes and to functional modules for adaptation and interference. CRISPR systems were then classified primarily on the basis of their concatenated Cas protein sequences and gene sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
194
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(198 citation statements)
references
References 34 publications
(105 reference statements)
4
194
0
Order By: Relevance
“…Using CRISPRstrand server, Alkhnbashi et al (2014) predicted the repeat orientations of multiple mature RNA species (crRNAs) for the identification and characterization of protospacers on genome invaders and regulatory motifs in the leader sequences of CRISPR arrays. Vestergaard et al (2014) also classified the cas subtypes based on cas-protein occurrences for archaea. Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using CRISPRstrand server, Alkhnbashi et al (2014) predicted the repeat orientations of multiple mature RNA species (crRNAs) for the identification and characterization of protospacers on genome invaders and regulatory motifs in the leader sequences of CRISPR arrays. Vestergaard et al (2014) also classified the cas subtypes based on cas-protein occurrences for archaea. Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013). Euryarchaea are more diverse phylogenetically than crenarchaea because of they are generally heterotophic in nature and frequent a wide range of natural environments (Vestergaard et al 2014). It suggested that many of their natural habitats are relatively rich in bacteria, rendering their CRISPR systems more susceptible to exchange between archaea and bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations